Vinylogous urethane vitrimers - Denissen, Wim (2015)
Vitrimers are a new class of polymeric materials with very attractive properties, since they can be reworked to any shape while being at the same time permanently cross-linked. As an alternative to the use of transesterification chemistry, we explore catalyst-free transamination of vinylogous urethanes as an exchange reaction for vitrimers. First, a kinetic study on model compounds reveals the occurrence of transamination of vinylogous urethanes in a good temperature window without side reactions. Next, poly(vinylogous urethane) networks with a storage modulus of ≈2.4 GPa and a glass transition temperature above 80 °C are prepared by bulk polymerization of cyclohexane dimethanol bisacetoacetate, m-xylylene diamine, and tris(2-aminoethyl)amine. The vitrimer nature of these networks is examined by solubility, stress-relaxation, and creep experiments. Relaxation times as short as 85 s at 170 °C are observed without making use of any catalyst. In addition, the networks are recyclable up to four times by consecutive grinding/compression molding cycles without significant mechanical or chemical degradation. Catalyst-free vitrimers based on the transamination of vinylogous urethanes are prepared from readily accessible chemicals. These high Tg, cross-linked materials exhibit excellent mechanical properties, while the exchangeable bonds enable full stress-relaxation on short time scales and recycling over many cycles.